The change as a way to activate innovation in the Algerian institutions - ZINE, YOUNESSE (Milev Journal of Research and Studies, 2016)
This study aims to identify the theoretical framework for innovation, and to address the theoretical concepts about the change and the management of change, and change is a matter of urgency to show the Algerian institutions and the difference between change and innovation, and to highlight the contribution of the change in the activation of innovation in the Algerian institutions. The study found a number of findings, including: that in order to contribute to the change in the activation of innovation in the Algerian institutions must follow a series of steps, including: the need to adopt a comprehensive strategy to change, to change the prevailing culture, the need to act in accordance with economic sense, the scientific mind in dealing with the problems, the need strengthen the relationship between the Algerian institutions, universities and research centers, the need to adopt innovative comprehensive strategy for the various aspects associated with the institution, a comprehensive global thinking and local action. A set of recommendations has been provided including: the Algerian institutions should review its self-assessment under the circumstances and changes rapidly, and to identify strengths and weaknesses and address the accumulation schedule of operations, regulations, policies and organizational and administrative procedures, prepared to face any unexpected challenges or unexpected, and activating the role of innovation through change and renewal of the laws and regulations such as establishing regulatory bodies to support the growth of innovative enterprises through the granting of appropriate licenses for various activities organized for those institutions